2016
DOI: 10.1111/nmo.12817
|View full text |Cite
|
Sign up to set email alerts
|

Vagal tone: effects on sensitivity, motility, and inflammation

Abstract: The vagus nerve (VN) is a key element of the autonomic nervous system. As a mixed nerve, the VN contributes to the bidirectional interactions between the brain and the gut, i.e., the brain-gut axis. In particular, after integration in the central autonomic network of peripheral sensations such as inflammation and pain via vagal and spinal afferents, an efferent response through modulation of preganglionic parasympathetic neurons of the dorsal motor nucleus of the vagus and/or preganglionic sympathetic neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 48 publications
(92 reference statements)
1
87
0
2
Order By: Relevance
“…There is however increasing indirect evidence, based on heart rate variability monitoring, to support an immune-modulatory role of the CAIP in humans (reviewed in 130,131 ). In healthy subjects, reduced heart rate variability indices (= low vagal tone) are independently associated with increased serum CRP and IL-6 levels and increased TNF and IL-6 production in endotoxin-stimulated whole blood.…”
Section: Human Evidencementioning
confidence: 99%
“…There is however increasing indirect evidence, based on heart rate variability monitoring, to support an immune-modulatory role of the CAIP in humans (reviewed in 130,131 ). In healthy subjects, reduced heart rate variability indices (= low vagal tone) are independently associated with increased serum CRP and IL-6 levels and increased TNF and IL-6 production in endotoxin-stimulated whole blood.…”
Section: Human Evidencementioning
confidence: 99%
“…Using this device, investigators have demonstrated efficacy at reducing sympathetic nerve activity in normal volunteers (Clancy et al, 2014). Another device, GammaCore (electroCore LLC, Basking Ridge, NJ) is hand-held and uses two disc electrodes for transcutaneous stimulation of the cervical vagus nerve (Bonaz et al, 2016c). Use of such non-invasive devices in treating chronic inflammatory diseases will need to consider patient compliance, which is also a concern with drug therapy (Bonaz et al, 2016c).…”
Section: Clinical Studies and Trialsmentioning
confidence: 99%
“…Another device, GammaCore (electroCore LLC, Basking Ridge, NJ) is hand-held and uses two disc electrodes for transcutaneous stimulation of the cervical vagus nerve (Bonaz et al, 2016c). Use of such non-invasive devices in treating chronic inflammatory diseases will need to consider patient compliance, which is also a concern with drug therapy (Bonaz et al, 2016c). The clinical efficacy of these approaches is currently under evaluation.…”
Section: Clinical Studies and Trialsmentioning
confidence: 99%
“…The results of this trial were published last July in Proceedings of the National Academy of Sciences 11 . Findings from another vagal-stimulation trial were published around the same time 12 . Bruno Bonaz, a gastroenterologist at the University Hospital in Grenoble, France, implanted stimulators into seven people with Crohn's disease.…”
Section: A Patient Approachmentioning
confidence: 95%